Evaluasi Kebijakan Program Bantuan Pangan Non Tunai (BPNT) di Desa Glagahan Kecamatan Perak Kabupaten Jombang - Daniar Seri Firdausi; Diana Hertati (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Non-Cash Food Assistance (BPNT) is food assistance that is distributed non-cash from the government to Beneficiary Families (KPM) every month, through an electronic account mechanism that is used only to buy food at places that have collaborated with association banks. However, in its implementation, BPNT still reaps many problems and obstacles. This study aims to determine the Policy Evaluation of the Non-Cash Food Assistance Program (BPNT) in Glagahan Village, Perak District, Jombang Regency. The type of research used by the author in this study is descriptive qualitative. The data sources of this research are primary data sources which are obtained from research informants and secondary data sources obtained from books, journals, and documents related to this research. Then the data collection techniques used in this study were interviews with purposive sampling method, direct observation (non-participants), and documentation with related data. In addition, the data analysis technique used is using interactive data analysis. As well as the validity of the data used in qualitative research, namely credibility (degree of trust), Transferability (transferability), Dependability (standard dependence), Confirmability (certainty). The results of this study found that the implementation of BPNT in Glagahan Village in its implementation was considered not optimal and overall good. It can be seen that in the aspects of efficiency, leveling, responsibility, and accuracy, the implementation is considered good and appropriate. Unfortunately, the effectiveness is assessed that the method of socialization and monitoring has not been carried out properly. In addition, in the aspect of focus on adequacy, BPNT is considered to be able to only provide limited benefits because the assistance received is not sufficient until the next period of assistance.